Path Finder Strategy Radar - Joshi, Manoj (Journal of Entrepreneurship, Business and Economics, 2016)
Purpose- The purpose of this research is to define and craft a “Path Finder Strategy” that can be adopted by firms, while entering into different markets with differentiated products. This conceptual yet a research paper covers an in-depth knowledge relating to devising a strategic ‘radar zone’ and assist in ascertaining whether a firm is product driven, market driven or customer driven (type of the firm). Design/methodology/approach- The learning from international evidences connected with the “type of the firm” has been extended to many firms operating in India. An exhaustive list of firms was stud-ied operating in India and five firms were picked that strongly reflected the drivers to strategy. Detailed case study followed by analysis was undertaken, while each driver to strategy was discovered that associated with a type of firm. Findings- There are unique drivers to strategy befitting each type of firm identified under product driven, customer driven and market driven firm. Thus, a “Path Finder Strategy” can be crafted for each type of firm. Research limitations/implications- There is a scope for discovering and connecting additional driv-ers’ to strategy associated with each type of firm. The research is confined to Indian Territory and firms operating within India, however, if global firms operating from different geographies could be studied for a more universal learning. Practical implications- Firm falling under a typical type of firm and thereby exhibiting a distinctive characteristics will have a unique “path finder strategy radar” based upon the industry it represents. Hence, firms can identify where the firms strategy is and should be to steer in the right direction. Originality/value- The research is based on field study and research at the primary and secondary level of investigations. Conceptual paper Reference to this paper should be made as follows: Joshi, M (2013). “Path Finder Strategy Radar”, Journal of Entrepreneurship, Business and Economics, Vol. 1 No. 1/2, pp. 17–34.